The Trust Game behind the Veil of Ignorance: A Note on Gender Differences - Jana Vyrastekova; Sander Onderstal (Tinbergen Institute, 2010)
We analyze gender differences in the trust game in a behind the veil of ignorance design. This method yields strategies that are consistent with actions observed in the classical trust game experiments. We observe that, on average, men and women do not differ in trust, and that women are slightly more trustworthy. However, men's strategies are bimodal, peaking at the subgame perfect Nash equilibrium and the Pareto efficient frontier, while women's strategies are single peaked at moderate transfers. For a given high level of pro-social preferences, men send more than women. This may be linked to men willing to bear more risk than women.
Keywords: C72; C91; 330; trust game; experiment; strategy method behind the veil of ignorance; gender differences; Ultimatumspiel; Geschlecht; Nichtkooperatives Spiel; Test